2022
DOI: 10.3390/healthcare10102079
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Socioeconomic Factors and Geriatric Syndromes on Frailty among Elderly People Receiving Home-Based Healthcare: A Cross-Sectional Study

Abstract: Purpose: To evaluate frailty and its relationship with geriatric syndromes in the context of socioeconomic variables. Patients and Methods: In this cross-sectional study, elderly people aged 65 years old and over who received homecare in the reference region of Crete, Greece, were enrolled. Geriatric syndromes such as frailty, dementia, and depression were evaluated using the SHARE-Frailty Index (SHARE-Fi), the Montreal Cognitive Assessment (MoCA), and the Geriatric Depression Scale (GDS), respectively. Level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
(35 reference statements)
0
1
0
1
Order By: Relevance
“…Pagyvenusių pacientų išgyvenamos emocijos. Pagyvenusio amžiaus žmonėms būdinga lėtinės ligos, polipatologija, specifiniai geriatriniai sindromai, problemų kompleksiškumas, todėl svarbus holistinis požiūris į esamas problemas, ilgalaikė priežiūra ir slauga [2]. Pagyvenusio amžiaus žmonės dažniau naudojasi sveikatos priežiūros įstaigų paslaugomis.…”
Section: Tyrimo Rezultataiunclassified
“…Pagyvenusių pacientų išgyvenamos emocijos. Pagyvenusio amžiaus žmonėms būdinga lėtinės ligos, polipatologija, specifiniai geriatriniai sindromai, problemų kompleksiškumas, todėl svarbus holistinis požiūris į esamas problemas, ilgalaikė priežiūra ir slauga [2]. Pagyvenusio amžiaus žmonės dažniau naudojasi sveikatos priežiūros įstaigų paslaugomis.…”
Section: Tyrimo Rezultataiunclassified
“…Tasioudi et al [ 14 ] identified the effect of frailty and geriatric syndromes, including comorbidities, on the quality of life of Greek people aged 65 years or older receiving home care. A second Greek study was conducted by Aravantinou-Karlatou et al [ 15 ]. They evaluated frailty and its association with geriatric syndromes (cognitive function, depression, and comorbidities) in the context of socioeconomic variables (e.g., education and annual income).…”
mentioning
confidence: 99%